Penerapan Nilai-Nilai Islam dalam Manajemen Sumber Daya Manusia - Rochaeni, Reni; Supendi, Pepen (BISMA : Business and Management Journal, 2024)
Human resource management plays an important role in the success of an organization, influencing productivity, efficiency, and reflecting the organization's values and principles. Islam provides relevant guidance for managing human resources in a fair, ethical, and sustainable manner, emphasizing the fulfillment of workers' rights, the creation of a supportive work climate, and integrity at work. Principles such as justice, work ethics, wise leadership, deliberation, and employee welfare are the main foundations in Islamic-based human resource management. This study uses a qualitative method with a literature review from the Qur'an, hadith, and references related to human resource management in Islam. Through content analysis, this study finds that the application of Islamic principles in HR management can create a fairer, harmonious, and productive work environment, which ultimately contributes to the well-being of all parties in the organization.